The Effect of Productive Subject Competencies Against Industrial Work Practices - I Nyoman Suputra; Lulu Nurul Istanti; Adietya Putra Pratama (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
the purpose of this study was to determine the suitability of students' productive learning competencies with the implementation of industrial work practices in SMK Muhammadiyah  5 Kepanjen,  Malang.. This research used  a descriptive qualitative approach. Data collection was obtained by conducting interview techniques, observation, and study documentation. The subjects of this study were the head of the industrial work practice program, the head of office management automation competency expertise,  students  of  XI  grade  at SMK Muhammadiyah 5 Kepanjen, and the DUDI. The results of this study  were  (1) the process of implementing industrial work practices began with planning by schools, testing the productive ability of students, debriefing, placement, checking, and pickup, (2) evaluation of industrial work practices in SMK Muhammadiyah 5 Kepanjen was done by asking the opinions of all those who participated in industrial work practices, but  it did not include DUDI in the valuation activities, (3) the competency of office automation and governance in SMK Muhammadiyah 5 Kepanjen was already relevant to DUDI demands but there were  several DUDI  still unable to provide relevant jobs with competencies held by students in office automation and governance.